2019
DOI: 10.1111/hsc.12900
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious growth among social work students: What makes the difference?

Abstract: This study examined the contribution of background variables, personal factors (professional commitment) and environmental factors (peer support and supervision) to social work students' vicarious growth as an implication of their field practicums with trauma victims. Special emphasis was placed on examining the role of secondary traumatisation in the growth process. The sample consisted of 259 social work students at three social work schools in Israel. All students conducted their field practicums in social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…A surprising finding was that satisfaction with clinical supervision was not a significant factor in the development of STS of VPTG. This is in contrast with previous studies of both student and qualified therapist samples, which have found that satisfaction with supervision has explained variance in growth (Ben-Porat et al, 2020); however, the current sample may have been more heterogenous in terms of expectations and experiences of supervision given the diverse backgrounds, work settings, and countries of practice included.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A surprising finding was that satisfaction with clinical supervision was not a significant factor in the development of STS of VPTG. This is in contrast with previous studies of both student and qualified therapist samples, which have found that satisfaction with supervision has explained variance in growth (Ben-Porat et al, 2020); however, the current sample may have been more heterogenous in terms of expectations and experiences of supervision given the diverse backgrounds, work settings, and countries of practice included.…”
Section: Discussioncontrasting
confidence: 99%
“…It is important to highlight, however, that the association between exposure and growth is more nuanced, as the level of clinician experience (i.e., years qualified) negatively predicted VPTG, which is contrary to the intuitive assumption that more vicarious exposure directly equates to more years of experience (Kjellenberg et al., 2014). One interpretation could be that the earlier stage of professional development and aspirations of newer therapists may lead to them processing their experiences more positively, enabling growth (Ben‐Porat et al., 2020). More experienced therapists who have been negatively impacted by therapy work may be more likely to reduce their level of trauma work or leave the profession completely (Pearlman & McIan, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, healthcare researchers have found that their programmes of study can themselves adversely affect student well-being (Hughes & Byrom, 2019). However, studies on social work education have shown that a challenging field practicum can enhance students' professional growth if they receive appropriate pedagogical support from their supervisors (Ben-Porat et al, 2020).…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Additionally, healthcare researchers have found that their programmes of study can themselves adversely affect student well‐being (Hughes & Byrom, 2019). However, studies on social work education have shown that a challenging field practicum can enhance students' professional growth if they receive appropriate pedagogical support from their supervisors (Ben‐Porat et al., 2020). Nursing mentors also experience challenges when guiding students from linguistic minorities (Oikarainen et al., 2018), and social work educators acknowledge difficulties with gay and lesbian students and seek ways of showing respect to minorities in pedagogical situations (Papadaki, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research regarding the helping process has focused on established helping professionals more than trainees with few studies describing positive changes, growth, and PTG experienced by trainee helping professionals, 2224 but none regarding positive responses related specifically to VPTG. It seems that the research that exists on harmful responses experienced by trainees is also limited and does not adequately explore how VT, MI, CF, STS, and burnout might apply; furthermore, existing research indicates that trainees require unique forms of support, but that such support is not consistently designed and provided.…”
Section: Introductionmentioning
confidence: 99%